Product Innovation Analysis at Nyai Cipelah Chips MSME - Sumiati, Ai; Nurmayanti, Ade Rima; Anwar, Muhammad Kaisar; Putri, Liza Aulia; Komala, Rini Noerfiany (Journal of Bussines Management Basic, 2026)
Nyai Cipelah Chips is a local small business that demonstrates how basic ingenuity and innovation can fuel growth, even with minimum funding. Founded in 2023 and called after the owner's nickname, "Nyai," and her village name, "Cipelah," the firm started as a simple fried food kiosk with capital of just IDR 500,000. The company has developed into a manufacturer of a variety of chip items that are marketed online, at MSME centers, local markets, and gift stores. Observations and interviews with the owner show that product innovation has played a crucial part in this development. The business experiments with diverse raw materials, introduces new and modern flavors, and continuously expands its product rangeThese efforts, combined with a strong focus on consistent quality, help the chips stand out in the local market. A noteworthy advance is the variety of ingredients. By employing multiple tubers and alternative materials, the business offers additional alternatives to consumers while lowering the danger of raw material shortages. Popular flavors such as numerous hot levels, balado, and savory spice blends also improve the product’s appeal. With five workers and a daily output of roughly five balls of chips, production is tiny but tightly maintained. Every stage is regulated to guarantee steady taste and texture, which builds consumer loyalty. bigger audiences without expensive promotional costs. Challenges exist, including variable raw material supply and escalating pricing. The owner must regularly alter sourcing and price tactics while competing with other local chip producers. To be competitive, the firm focuses on flavor uniqueness and quality enhancement. Overall, product innovation has considerably enhanced the expansion of Keripik Nyai Cipelah. With its focus to quality, inventive flavors, and adaptable marketing, the business is well-positioned to continue growing as a strong local brand.